Novel O-acylated (E)-3-aryl-6, 7-dihydrobenzisoxazol-4(5H)-one oximes targeting HSP90-HER2 axis in breast cancer cells. (1st January 2022) - Piven, Yuri A.; Yastrebova, Margarita A.; Khamidullina, Alvina I.; Scherbakov, Alexander M.; Tatarskiy, Victor V.; Rusanova, Julia A.; Baranovsky, Alexander V.; Zinovich, Veronica G.; Khlebnicova, Tatyana S.; Lakhvich, Fedor A.
Graphical abstract: Abstract: Novel O -acylated ( E )-3-aryl-6, 7-dihydrobenzisoxazol-4(5 H )-one oximes were designed as potential HSP90 inhibitors. A series of the compounds was synthesized by oximation of ( E )-3-aryl-6, 7-dihydrobenzisoxazol-4(5 H )-ones followed by O -acylation with acylamidobenzoic acids. The obtained compounds showed an antiproliferative effect on three breast cancer cell lines (MCF7, MDA-MB-231 and HCC1954). Compound 16 s exhibited high antiproliferative potency against HCC1954 breast cancer cells with the IC50 value of 6 µM was selected for in-depth evaluation. Compound 16 s did not inhibit the growth of normal epithelial cells. We have demonstrated that the compound 16 s can induce apoptosis in cancer cells via inhibition of HSP90 "client" proteins including a key oncogenic receptor, HER2/neu. Described here compounds can be considered for further basic and preclinical investigation as a part of HSP90/HER2-targeted therapies.